2007
DOI: 10.1104/pp.106.096446
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Arbuscular Mycorrhization by Carbon. The Symbiotic Interaction Cannot Be Improved by Increased Carbon Availability Accomplished by Root-Specifically Enhanced Invertase Activity

Abstract: The mutualistic interaction in arbuscular mycorrhiza (AM) is characterized by an exchange of mineral nutrients and carbon. The major benefit of AM, which is the supply of phosphate to the plant, and the stimulation of mycorrhization by low phosphate fertilization has been well studied. However, less is known about the regulatory function of carbon availability on AM formation. Here the effect of enhanced levels of hexoses in the root, the main form of carbohydrate used by the fungus, on AM formation was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
1
10
1
Order By: Relevance
“…The observation that SUT1antisense plants did not differ in their extent of AM fungal root colonization from corresponding WT plants in our study is in disagreement with earlier findings of Schaarschmidt et al (2007a), who observed a decrease in the extent of AM fungal root colonization in tobacco plants with impaired pyrophosphate-dependent uptake of sucrose into the phloem. Since different plant species and different approaches to impairing plant phloem loading of sucrose were used in the two studies, it is possible that overall sucrose flux from source to sink organs was different between the transformants used in the two experiments, e.g.…”
Section: • •contrasting
confidence: 82%
See 2 more Smart Citations
“…The observation that SUT1antisense plants did not differ in their extent of AM fungal root colonization from corresponding WT plants in our study is in disagreement with earlier findings of Schaarschmidt et al (2007a), who observed a decrease in the extent of AM fungal root colonization in tobacco plants with impaired pyrophosphate-dependent uptake of sucrose into the phloem. Since different plant species and different approaches to impairing plant phloem loading of sucrose were used in the two studies, it is possible that overall sucrose flux from source to sink organs was different between the transformants used in the two experiments, e.g.…”
Section: • •contrasting
confidence: 82%
“…The absence of differences in extra-and intraradical development between SUT1sense and WT plants grown under Low P supply, suggests that under conditions where the host plant relies on the AM symbiosis for P uptake, SUT1sense and WT plants did not differ in the amount of C transferred to the AM symbiosis. Similarly, Schaarschmidt et al (2007a) could not improve AM fungal performance by increasing hexose concentrations in the root apoplast of transgenic tobacco plants with root-specifically enhanced invertase activity. The authors concluded that under conditions of limited plant P availability, WT plant C supply to the AM fungus may already be sufficient for optimal AM development.…”
Section: • •mentioning
confidence: 89%
See 1 more Smart Citation
“…Genes encoding apoplastic invertases as well as sucrose synthases are induced in mycorrhized plants and the gene products could be localised in regions of the root cortex where cells are colonised by the fungus (Blee and Anderson, 2002;Hohnjec et al, 2003;Schaarschmidt et al, 2006). Moreover, down regulation of such genes resulted in decreased formation of AM fungal structures in the roots (Schaarschmidt et al, 2007;Baier et al, 2010). Comparison of mycorrhizal with control roots revealed that fructose contents were increased, while glucose contents were not different.…”
Section: Discussionmentioning
confidence: 95%
“…In return, up to 20% of the plant-fixed carbon is transferred to the fungus [27]. Hexoses formed from carbon taken up by the root were found to be the major form of carbohydrates by AMF [45]; however, triacylglycerol is the main form of stored carbon utilized by the mycobiont during all stages of its life cycle [93]. …”
Section: Essential and Regulatory Roles Of “Bio-signals”mentioning
confidence: 99%